A TYPE OF DWARFISM FOUND IN SOUTH BENGKULU TO BE AN X-LINKAGE - MUSLIM, CHOIRUL; KARYADI, BHAKTI; RUYANI, ACENG; PURNAMAWATI, ICE; -, HERNANI; -, SUMIYATI (Jurnal Biologi Udayana; Vol 12 No 2 (2008): JURNAL BIOLOGI, 2008)
We have reported here a specific human short stature population in Kedurang District, South Bengkulu. AH those are men, described as a mild dwarf (130-150 cm), detected after 5 to 10 years old, caused by the failure on lumbar backbone growth and development, and only found among the men. In this investigation, we examine the inheritance pattern of the dwarfism by using pedigree analysis, study the morphological comparison between the disorder and normal person, and finally we ascertain the variation among the disorder. We accomplished a survey on pedigree family to at least 3-4 generations related to the disorder. The data are then tested with Chi-square test, and transformed to tree families and pedigree analysis. To investigate morphological performance and their variation, we collected morphometric measurements to both disorder and normal group of sample; they are the height, the vertebral bones length, head measurement, the leg and arm length (upper and fore side), and their indexes. The data were analyzed descriptively. To find out the variation, the quantitative expression and penetrance, we evaluated the data according to normal distribution with Z test. The result showed all the dwarfisms in Kedurang are men, who inherited his gene from his carrier mother. As a result, the gene has tightly linked to X chromosome and supposedly belongs to Spondylo Epiphypeseal Dysplasia Tarda (SEDT). These were concluded from 32 related family of dwarfism. We found 19 dwarf persons, grouped into young, adult, and older persons. The their height were shorter than normal (136,5 cm), and the length of vertebrae was under normal value (51,5 cm). Their frontal extremity were shorter than the normal one, but they are in proportion with any part comprised them. Their feet were shorter, but the proportion of leg is longer than calf. The rest is as normally. Among the dwarf person, there are variations of the length. The phenotypic expressivity is varied in the vertebrae, leg, and calf; but the rest is relatively invariable. Their penetrance is strong, mostly in the height, length of vertebrae, and legs. Based on morphological data we concluded that the disorder in the Kedurang, South Bengkulu belongs to SEDT (Spondyloepiphyseal dysplasia tardd).
Keywords: Short stature; lumbar backbone; dwarf x-linkage